The business of being a professional sportsperson: a taxing question / Chris Davies - Davies, Chris (Faculty of Sports Science and Recreation, 2011)
Sport at the beginning of the 21st century, is very different from the turn of the 20th century, one of the major differences being the great increase in the level of professional sport due to the dramatic increase in television revenue, particularly from pay television. In Australia, this rise in professional sport has seen a number of taxation cases involving sportspersons reach the High Court. The outcome of these cases is that the revenue attained by Olympic athletes in the form of grant money, prizemoney and sponsorships is now considered to be taxable income, while payments to managers to obtain playing contracts and other income are deductible expenses. It is also suggested that these cases have highlighted the fact that sports law is, in effect, all areas of law applied to the sporting context, and that this context can be a significant aspect of the case.